Daily Activities of Proboscis Monkey Nasalis larvatus in Bekantan Ecotourism Area, Tapin District, South Kalimantan - Yuono Prasetyo, Catur; Saragih, Novera Fatmi; Rohim; Ilmi, Zainal (BIO PALEMBANICA, 2024)
The Proboscis Monkeys Nasalis larvatus is endemic primate of Borneo Island. Research on the daily activities of Proboscis Monkey using the focal animal sampling method through direct observation of animal behavior by referring to the ethogram that has been carried out in Muning River, Tapin Regency, South Kalimantan Province; which is adjacent to the operational canal owned by PT. Antang Gunung Meratus (AGM). This research was conducted from May to October 2024 with a total of 4,528 minutes observation. The results of the study show the daily behavior of Proboscis Monkeys is highest in resting activities with an average of 61.66%, followed by eating activities with an average of 23.21% which were observed mostly to eat Galam trees Melaleuca leucadendra. This caused the existing conditions in Bekantan ecotourism area of PT. AGM are dominated by this species, then followed by moving activities with an average of 8.17%, and the least social activities with an average of 6.96%.